POTRET KEMEROSOTAN MORAL DALAM DUNIA PENDIDIKAN INDONESIA: SEBUAH KRITIK DARI ABDURRAHMAN - ROHMAN, ARIF (FOUNDASIA, 2015)
The education is convinced to play an important role in solving and providing the way out upon the present social problem. One of the important results of educational implementation is the progress of science and technology proved to be able to assist mankind in solving the problem. Ironically, if the educational implementation practice it self contains the problem, for example degradation of morality in education. Therrfore, it, order to solve such a condition, an effort is needed to reconstruct morality to return the main mission of education fur the manifestation of the Indonesian societal typology which is within morality and just prosperity